MICROPROPAGATION OF BANANA CV. MALBHOG - SUGANDH SUMAN; HARSH KUMAR (The Bioscan, 2015)
Malbhog, one of the most important and delicious local cultivar of banana in Bihar, is on verge of becoming extinct because of panama wilt and non-availability of disease free quality propagules. The culture of shoot tips taken from suckers on Murashige and Skoog (MS) medium supplemented with different concentrations and combinations of Indole acetic acid (IAA) and Benzyl amino purine (BAP) resulted in differentiation of adventitious shoots. The maximum differentiation of shoots (92.05 %) was observed on MS medium with 0.57 μM IAA and 17.74 μM BAP. The number of shoots per culture was 16.75. The subculture of differentiated shoots on the same medium resulted in further differentiation (91.97 %) of more than 15 shoots per culture. The in vitro developed shoots showed 100% rooting on MS medium supplemented with 4.92 μM Indole butyric acid (IBA). The plantlets were acclimatized and field transferred. A suitable and efficient protocol for micropropagation of Malbhog cultivar of banana was developed.